2008
DOI: 10.1111/j.1532-849x.2008.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Prosthodontic Program Directors' Perceptions Regarding Implant Placement by Prosthodontic Residents: A 2004 Survey Conducted by the Educational Policy Subcommittee of the American College of Prosthodontists

Abstract: This survey showed that implant dentistry has become an integral part of the postgraduate prosthodontic curriculum. The trends to incorporate implant placement into the postgraduate prosthodontic curriculum were already evident prior to 2004. To address the demand for implant treatment in patient care and enhance surgical implant knowledge, the ACP in 2005 added placement of implants to its Accreditation Standards for Advanced Specialty Education Programs in Prosthodontics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Implant placement in an AEP program can provide successful results. A 2004 survey conducted by the Educational Policy Subcommittee of the ACP examined the implant curricula in AEP programs based on the perceptions of program directors 24 . That study reported that implant dentistry is an integral part of AEP curricula, and noted the incorporation of implant surgical training in the program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Implant placement in an AEP program can provide successful results. A 2004 survey conducted by the Educational Policy Subcommittee of the ACP examined the implant curricula in AEP programs based on the perceptions of program directors 24 . That study reported that implant dentistry is an integral part of AEP curricula, and noted the incorporation of implant surgical training in the program.…”
Section: Discussionmentioning
confidence: 99%
“…A 2004 survey conducted by the Educational Policy Subcommittee of the ACP examined the implant curricula in AEP programs based on the perceptions of program directors. 24 That study reported that implant dentistry is an integral part of AEP curricula, and noted the incorporation of implant surgical training in the program. This study examined the survival rate of dental implants placed and restored exclusively by prosthodontic residents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, to address the demands for implant treatment in patient care and to enhance surgical implant knowledge, the ACP in 2005 added placement of implants to its Accreditation Standards for Advanced Specialty Education Programs in Prosthodontics. 17 It is expected that students will act as first assistant and/or primary surgeon for some of their own patients. In respect to TMD, recent accreditation standards for AEP programs mandated that instructions must be provided at the understanding level in TMD and orofacial pain, and students must be competent in the prosthodontic management of patients with TMD and/or orofacial pain.…”
Section: Program Specificsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Studies related to AEP have been based on surveys of program directors, deans, and practicing prosthodontists. [15][16][17][18][19] A recent study for the first time surveyed AEP residents on which factors might influence residents in choosing prosthodontics as their specialty. 20 The study reported that residents considered the complexities and challenges of treatment planning and execution of prosthodontic treatment to be the most important factors in deciding to specialize in prosthodontics.…”
mentioning
confidence: 99%